Chlorine/UV Process for Decomposition and Detoxification of Microcystin-LR - Zhang, Xinran; Li, Jing; Yang, Jer-Yen; Wood, Karl V; Rothwell, Arlene P; Li, Weiguang; Blatchley III, Ernest R (Environmental science & technology, 2016)
Microcystin-LR (MC-LR) is a potent hepatotoxin that is often associated with blooms of cyanobacteria. Experiments were conducted to evaluate the efficiency of the chlorine/UV process for MC-LR decomposition and detoxification. Chlorinated MC-LR was observed to be more photoactive than MC-LR. LC/MS analyses confirmed that the arginine moiety represented an important reaction site within the MC-LR molecule for conditions of chlorination below the chlorine demand of the molecule. Prechlorination activated MC-LR toward UV254 exposure by increasing the product of the molar absorption coefficient and the quantum yield of chloro-MC-LR, relative to the unchlorinated molecule. This mechanism of decay is fundamentally different than the conventional view of chlorine/UV as an advanced oxidation process. A toxicity assay based on human liver cells indicated MC-LR degradation byproducts in the chlorine/UV process possessed less cytotoxicity than those that resulted from chlorination or UV254 irradiation applied separately. MC-LR decomposition and detoxification in this combined process were more effective at pH 8.5 than at pH 7.5 or 6.5. These results suggest that the chlorine/UV process could represent an effective strategy for control of microcystins and their associated toxicity in drinking water supplies.